ANALISIS PENERAPAN TOTAL QUALITY MANAGEMENT DALAM MENJAGA KUALITAS PRODUK AIR MINERAL DALAM KEMASAN MEREK SABINA PADA PT. SABINA TIRTA UTAMA SAMARINDA - Filda Ramadani (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2020)
This researcher is motivated by analyzing the application of Total Quality Management well in a in industrial company in maintaining the quality of the products produced at PT. Sabina Tirta Utama, Through the application of TQM it is expected that the company can provide satisfaction to customers with the result produced. The formulation of the problem in this study is divided two into: (1) Analyzing the application of TQM in maintaining the quality of the products produced at PT. Sabina Tirta Utama. (2) Whether the quality produced is in accordance with standard SNI. This study ams to find out how the application of TQM at PT. Sabina Tirta Utama and to find out the quality the products produced at PT. Sabina Tirta Utama.Intense competition will require companies to provide quality product to consumers. But the company’s concern is not limited to the quality of the product produced, but also on aspeets of the process, human resources (HR) and the environment. PT. Sabina Tirta Utama is a company that produces bottled mineral water in Samarinda and faces competition in a business that is growing increasingly. One of the methods carried out by PT. Sabina Tirta Utamain order to remain competitive by implementing Total Quality Management (TQM) . through an obsession toward quality, teamwork, continus system improvement, education and training, unity of purpose, and employee involvement. TQM is a system to achive the goals of an organization, one of which is maintaining product quality.Based on the result of interviews and observations, implementation of TQM in maintaining the quality of bottled mineral water products at PT. Sabina Still has reject products every month and teamwork is still careless in packing. Then As the result quality of bottled mineral waterproduced by PT. Sabina Tirta Utama has met the standard.